2017
DOI: 10.1038/scsandc.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility pilot using telehealth videoconference monitoring of home-based NMES resistance training in persons with spinal cord injury

Abstract: The pilot work documented that using telehealth communication is a safe, feasible and potentially cost-reducing approach for monitoring home-based NMES-RT in persons with chronic SCI. All trained muscles showed detectable muscle hypertrophy with concomitant decrease in ectopic adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…The quadriceps and hamstring ratios are similar to those reported by Housh et al who found that the quadriceps represented ~52 % and the hamstrings represented ~19 % of the total muscle CSA in nonSCI individuals [13]. These findings may explain why previous work has primarily focused on training the quadriceps muscle to evoke hypertrophy with an emphasis on improving the metabolic profile [9][10][11]. Based on the current findings the size of the quadriceps is double the size of either the hamstrings or adductors.…”
Section: Discussionsupporting
confidence: 88%
“…The quadriceps and hamstring ratios are similar to those reported by Housh et al who found that the quadriceps represented ~52 % and the hamstrings represented ~19 % of the total muscle CSA in nonSCI individuals [13]. These findings may explain why previous work has primarily focused on training the quadriceps muscle to evoke hypertrophy with an emphasis on improving the metabolic profile [9][10][11]. Based on the current findings the size of the quadriceps is double the size of either the hamstrings or adductors.…”
Section: Discussionsupporting
confidence: 88%
“…We have tested the feasibility of home-based NMES-RT over an eight-week period utilizing video-telecommunication service. The result showed that the trained knee extensor muscle CSA increased by 18% compared to the controlled limb [78]. This may serve as a continuation of the current trial and bases for establishing future home-based clinical trials to maximize recruitment and reduce the cost associated with travel time.…”
Section: Limitationsmentioning
confidence: 72%
“…The results of the current review study indicated that RPM plays a role in prevention and control of many complications in patients with SCI ( Table 1). The results of investigations revealed that telehealth and nervous diseases and technological advancements could make the health care convenient and economic in such patients by easy access to the program (10,31,38). The findings indicated that telemedicine is effective in patients with nervous disorders and it can decrease the rehospitalization time (16,17).…”
Section: Discussionmentioning
confidence: 99%